Orthodontists' perception and attitude toward accelerated orthodontic treatments in Australia - Hatami Amir; Naoum Steven; Lee Richard J.H; Razza John M.; Goonewardene Mithran S. (Sciendo, 2024)
The purpose of this cross-sectional study was to survey the perception and attitude of Australian orthodontists toward accelerated orthodontic treatments.